HIV incidence is rapidly increasing with age among young men who have sex with men in China: a multicentre cross‐sectional survey. Issue 8 (19th June 2018) - Mao, X; Wang, Z; Hu, Q; Huang, C; Yan, H; Wang, Z; Lu, L; Zhuang, M; Chen, X; Fu, J; Geng, W; Jiang, Y; et al.
Abstract : Objectives: The HIV epidemic is worsening among men who have sex with men (MSM) in China, especially among those who are younger than 25 years old [younger MSM (YMSM)]. The aim of the study was to compare the prevalences of HIV incidence and recent HIV infection as well as factors associated with recent HIV infection in YMSM and older MSM (OMSM). Methods: A multicentre cross‐sectional survey was conducted among 4496 MSM recruited from seven Chinese cities. YMSM were defined as those aged < 25 years. Data on demographics and sexual behaviours were collected using structural questionnaires. Blood samples were tested for recent HIV infection and other sexually transmitted infections. Results: Among the participants, 1313 were YMSM and 3183 were OMSM. Compared with OMSM, YMSM had a higher prevalence of recent HIV infection [5.4% (71 of 1313) for YMSM vs . 3.6% (115 of 3175) for OMSM; P = 0.006] and a higher HIV incidence [11.8 per 100 person‐years (PY) (95% confidence interval (CI) 9.0–14.5) for YMSM vs . 7.6 per 100 PY (95% CI 6.3–9.0) for OMSM]. The incidence increased with age among YMSM, especially between the ages of 16 and 21 years. In contrast, the incidence declined with age among OMSM. Anal bleeding, recreational drug use, syphilis and herpes simplex virus 2 (HSV‐2) infection were independent risk factors for recent HIV infection among YMSM. The prevalence of all these risk factors increased with age between the ages of 16 and 21 years. Anal bleeding (19.8%) and recreational drug use (19.5%) had the highest adjusted population attributable fractions (aPAFs) among YMSM. The highest aPAFs of anal bleeding (27.4%) and syphilis infection (25.5%) were found between the ages of 19 and 21 years. Conclusions: The HIV incidence in Chinese YMSM was significantly higher than that in OMSM. YMSM aged 16–21 years had an extremely high risk of recent HIV infection.